Optical Response of Sila-Fulleranes in Interaction With Glycoproteins for Environmental Monitoring - Qasemnazhand, Mohammad; Khoeini, Farhad; Marsusi, Farah (Frontiers in Physics, 2021)
In this paper, we introduce new features of silicon in fullerane structures. Silicon, when placed in a fullerane structure, increases its electron affinity and electrophilicity index, compared to placement in a diamondoids structure. These nanoparticles can be used to make optical sensors to detect viral environments. In this work, we theoretically examine the changes in the UV-Visible spectrum of sila-fulleranes by interacting with viral spikes. As a result, we find out how the color of silicon nanoparticles changes when they interact with viruses. We apply N- and O-Links for viral glycoprotein structures, and Si20H20 silicon dodecahedrane, respectively. Our computational method to obtain optimal structures and their energy in the ground and excited states, is density functional theory (DFT). Besides, to get the UV-Visible spectrum, time-dependent density functional theory (TD-DFT) approach has been used. Our results show that the color of sila-dodecahedrane is white, and turns green in the face of viral spikes. We can use the optical sensitivity of silicon nanoparticles, especially to identify environments infected with the novel coronavirus.